Analysing the combination of cost reduction techniques in Android mutation testing. (24th March 2021) - Polo‐Usaola, Macario; Rodríguez‐Trujillo, Isyed
Summary: When applied to mobile software, mutation testing is particularly costly due to the deployment of the app under test onto the device: if one deployment is made for each generated mutant, the execution time becomes unapproachable. This paper analyses how the combination of different cost reduction techniques improves the execution time of mutation testing in mobile apps. The techniques reviewed and combined are mutant schema, parallel execution and two different ways of executing tests against the mutants ( all against all and all against mutants remaining alive ), as well as greedy algorithm for reducing the test suite size. This paper also presents a mathematical model of cost reduction and checks its validity with several experiments. Furthermore, the exhaustive and long experimentation has led the authors to compile a set of good practices which are also presented in a set of lessons learned. Abstract : The article is focused on the reduction of the total execution time in mutation testing of mobile applications. We apply several combinations of test execution techniques and propose a mathematical model to predict the testing time. The article also provides a wide set of good practices and lessons learned for mutation testing.